Legal Regulatory Mechanism of Social Relations for Ensuring Dynamics in Civil Relationship - KOSTRUBA, Anatoliy V. (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
Article is dedicated to the study of the legal regulatory mechanism of social relations, namely one of its elements – legal relations. The purpose of the article is to define the legal regulatory mechanism of social relations, its elements, and to study civil relations and legal facts as an integral part of this mechanism. The study also seeks to understand properties and features of regulatory legal facts in the legal regulatory mechanism. The article considers the structure and properties of elements of the legal regulatory mechanism of civil relations. As a separate question the article considers customary laws as the main source of law regulating social relations. The author examines legal relations through the lenses of legal acts and, in particular, the enforcement and regulation of legal facts, which is, certainly, a new way of looking at the legal nature of a specified mechanism. Likewise, the article examines currently existing gaps in scientific rationale of the legal regulatory mechanism of social relations in Ukraine.